Правове регулювання застосування фітосанітарних заходів у сільському господарстві України - Боснюк, Юлія Павлівна (Одеса, 2023)
У дисертації здійснено комплексний науковий аналіз правового регулювання застосування фітосанітарних заходів у сільському господарстві України, сформульовано теоретичні узагальнення та практичні пропозиції, що загалом вирішують важливе наукове завдання і спрямовані на вдосконалення нормативного забезпечення відповідних суспільних відносин. У дисертації встановлено теоретико- методологічні та правові засади фітосанітарної безпеки України. Визначено ключові правові поняття (фітосанітарний ризик, фітосанітарні заходи, фітосанітарна безпека). Визначені та охарактеризовані етапи еволюційного становлення фітосанітарного законодавства України.

Запропоновано розширити законодавче визначення фітосанітарних заходів. Сформульовано на основі аналізу іноземного досвіду комплексний підхід до поступового зниження хімізації сільського господарства, згідно з яким пропонується поєднання адміністративних, економічних та інформаційних важелів. Аргументовано, що подальше удосконалення фітосанітарного законодавства України залежить від якісного втілення концепції інтегрованого захисту рослин. Доведено, що конкретний прояв концепція інтегрованого захисту має знайти у закріпленні комплексу правових механізмів та вимог, а саме: а) обов’язкова та регулярна агрохімічна паспортизація сільськогосподарських земель; б) використання «шлюзового принципу» під час здійснення фітосанітарних заходів; в) використання селекційних біотехнологічних фітосанітарних заходів на постійній основі, а застосування генетичних біотехнологічних прийомів – лише за умови реалізації принципу перестороги.

In the dissertation, a comprehensive scientific analysis of the legal regulation of the application of phytosanitary measures in the agriculture of Ukraine was carried out, theoretical generalizations and practical proposals were formulated, which generally solve an important scientific task and are aimed at improving the regulatory support of relevant social relations. The thesis establishes the theoretical, methodological and legal principles of phytosanitary safety of Ukraine. Key legal concepts (phytosanitary risk, phytosanitary measures, phytosanitary safety) are defined. The stages of evolutionary formation of phytosanitary legislation of Ukraine are defined and characterized.

It is proposed to expand the legal definition of phytosanitary measures, under which it is proposed to understand: a) measures to prevent the appearance and spread of quarantine organisms, b) measures aimed at limiting the economically unfavorable impact of regulated non-quarantine organisms, c) measures that indirectly (indirectly) contribute to the protection of plants, form the conditions necessary for this (use of fertilizers, growth stimulants, etc.). Based on the analysis of foreign experience, a comprehensive approach to the gradual reduction of agricultural chemicalization is formulated, according to which a combination of administrative, economic and informational levers is proposed. It is argued that the further improvement of the phytosanitary legislation of Ukraine depends on the chosen content of the updated legislative provisions, namely: the qualitative implementation of the concept of integrated plant protection, which consists in the formation of an optimal set of phytosanitary measures, with the aim of increasing efficiency and reducing the negative impact on the environment and humans. It has been proven that the concept of integrated protection should find a concrete manifestation in the establishment of a set of legal mechanisms and requirements, namely: a) mandatory and regular agrochemical certification of agricultural lands; b) use of the "gateway principle" during phytosanitary measures; c) the use of selective biotechnological phytosanitary measures on a permanent basis, and the use of genetic biotechnological methods - only under the condition of implementation of the precautionary principle.

The most optimal methodological principles of legal regulation of the implementation of phytosanitary measures in agriculture are substantiated: 1) balance of economic, ecological and social interests; 2) cooperation between the state and society in the field of ensuring phytosanitary safety; 3) preservation of national legal sovereignty in the conditions of international legal processes; 4) technical and scientific validity of the application of phytosanitary measures; 5) ecological imperative as a measure of fairness of phytosanitary legislation.

The system of comprehensive state support for producers seeking to be certified according to private standards is substantiated, which should include five areas: a) financial support (provision of targeted loans); b) service support; c) informational and consulting support (distribution of relevant and available information, creation of information portals); d) personnel support (updating the professional education of specialists in the implementation of phytosanitary measures); e) support of cooperation of producers.

The periodization of the institutional and functional provision of phytosanitary security in Ukraine has been improved, taking into account the latest changes and trends: 1) the stage of differentiation (1991-2012), which was characterized by: a) growing pluralism of management and control bodies and institutions; b) overlapping of powers and competences; 2) the stage of specialization (2012-2016), which was characterized by: a) unification of powers in several key bodies; b) preservation of problems of duplication and unclear demarcation of powers; 3) the stage of unification (2016 - until today), which was marked by the formation of the State Production and Consumer Service as a qualitatively new service inspection body that combines control powers with service ones.

The prematurity of the integration of individual requirements of private law regulation into the system of phytosanitary legislation of Ukraine is argued on the basis of the identified "life cycle" of private standardization: a) embryonic state (private standards do not significantly affect the actual industrial phytosanitary relations); b) scaling (a legal regulation parallel to the state one is created); c) legitimization (harmonization and combination of state and private regulation of phytosanitary relations).

The characteristic features of the legal support for the production of pesticides and agrochemicals have been identified: a) mandatory state registration of the preparative form of pesticides and agrochemicals; b) ecological and institutional subordination, which emphasizes the priority of the preventive function at the stage of formation and admission of new phytosanitary preparations; c) combination of transparency with requirements for protection of drug rights; d) reservation of the possibility to cancel the registration of a pesticide or agrochemical.
Боснюк Ю. П. Правове регулювання застосування фітосанітарних заходів у сільському господарстві України : дис…канд. юрид.наук / Боснюк, Юлія Павлівна ; Національний університет «Одеська юридична академія» – Одеса, 2023. – с. 263
Keywords: фітосанітарні заходи; фітосанітарна безпека; сільське господарство; шкідники; захист рослин; пестициди; агрохімікати; аграрне право; phytosanitary measures; phytosanitary safety; agriculture; pests; plant protection; pesticides; agrochemicals; agrarian law